2023
DOI: 10.1038/s42003-023-04933-9
|View full text |Cite
|
Sign up to set email alerts
|

The SWine IMputation (SWIM) haplotype reference panel enables nucleotide resolution genetic mapping in pigs

Abstract: Genetic mapping to identify genes and alleles associated with or causing economically important quantitative trait variation in livestock animals such as pigs is a major goal in animal genetic improvement. Despite recent advances in high-throughput genotyping technologies, the resolution of genetic mapping in pigs remains poor due in part to the low density of genotyped variant sites. In this study, we overcame this limitation by developing a reference haplotype panel for pigs based on 2259 whole genome-sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…4; supplementary Table S15 and S16). Due to limited space, BMP2 particularly stands out for its strong association with growth traits in pigs (Li et al 2021; Ding et al 2023). This gene is located within regions indicative of introgression between Southern Chinese indigenous pigs and Canadian Duroc or Pietrain (defined as regions where rIBD > 0).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4; supplementary Table S15 and S16). Due to limited space, BMP2 particularly stands out for its strong association with growth traits in pigs (Li et al 2021; Ding et al 2023). This gene is located within regions indicative of introgression between Southern Chinese indigenous pigs and Canadian Duroc or Pietrain (defined as regions where rIBD > 0).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous body length genome-wide association study (GWAS) (Ding et al 2023), we identified a high-confidence candidate variant (chr17:15643342:C>T) located upstream of the BMP2 gene. Given the high correlation coefficient between body length and body height (supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, reference panels are large and diverse, such as the 1000 Genomes Project [9], the UK10K Project [10], the Genome of the Netherlands [11], 64976 human haplotypes from European ancestry [12], and ChinaMAP [13], so that the imputation accuracy based on them could be high. Livestock panels have been reported in pigs [14,15] and cattle [16] but were not publicly available. The establishment of both an efficient imputation pipeline and a public reference panel on cattle is crucial for research and cattle breeding improvement.…”
Section: Introductionmentioning
confidence: 99%